The Attitudes of Art Education Teachers towards the use of AI in Teaching Visual Arts at General Education Stages in the Kingdom of Saudi Arabia - Ali, Nouradeen Aisa Adam (Journal of Ecohumanism, 2024)
This study aimed to study the attitudes of art education teachers towards the use of AI in teaching visual arts at the general education levels in the KSA. The study sample consisted of 144 art education teachers at the general education levels in the KSA. The study relied on the descriptive analytical approach, as the study used the questionnaire as a tool to achieve its objectives, for a random sample of art education teachers, where a questionnaire was prepared and developed related to the attitudes of art education teachers towards the use of AI in teaching visual arts. The results showed that the average knowledge of art education teachers about AI techniques in the field of education was about 3.43, while the average general attitudes of art education teachers towards integrating AI into the teaching process was about 4.69, while the average potential benefits of using AI in teaching art education from the teachers' was about 4.75, the average challenges and difficulties facing art education teachers when applying AI techniques was about 4.7, while the attitudes of art education teachers towards the use of AI in teaching visual arts at the general education stages in the KSA were strongly agree, with an average of 4.39. It also showed that there were no statistically significant differences between the average attitudes of art education teachers towards the use of AI in teaching visual arts in general education in the Kingdom of Saudi Arabia in the study sample according to (gender, academic qualification, and years of experience).